Civic education: A priority for the new university curriculum - Ferrer, Dilian (Omnia, 2024)
Today it is significant to reflect on how education has become a matter of great concern and within its difficulties is the sense of adequately guiding citizen education to coexist in society and the world with ethical and democratic values. Contemporary times give us an account of the multiple changes that are taking place and the problems that are registered in society and the citizen is called to face these difficulties. Training citizens is a vital matter because it has been neglected within the sphere of formal and informal education, for this reason these reflections are presented, supported by hermeneutic interpretative analysis. Currently it is a priority to address the problems within the Social Sciences to make adequate proposals that are incorporated into the curricular reform that begins at the University of Zulia